2006
DOI: 10.1016/j.jacc.2006.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Post-Reperfusion Myocardial Infarction

Abstract: Acadesine is the first therapy proven to be effective for reducing the severity of acute post-reperfusion MI, substantially reducing the risk of dying over the 2 years after infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(25 citation statements)
references
References 26 publications
1
22
1
1
Order By: Relevance
“…Indeed, there are many studies on human myocardium showing that ischaemic preconditioning can be elicited in experimental conditions, and protects against standardised ischaemic and reperfusion insult [22][23][24]. The same was shown with various forms of pharmacological preconditioning [25][26][27][28]. Currently, no experimental study has shown that human myocardium can be remotely preconditioned against standardised ischaemic/hypoxic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are many studies on human myocardium showing that ischaemic preconditioning can be elicited in experimental conditions, and protects against standardised ischaemic and reperfusion insult [22][23][24]. The same was shown with various forms of pharmacological preconditioning [25][26][27][28]. Currently, no experimental study has shown that human myocardium can be remotely preconditioned against standardised ischaemic/hypoxic insult.…”
Section: Discussionmentioning
confidence: 99%
“…Acadesine, a drug thought to increase adenosine levels in ischemic tissues, was compared with placebo in 2,698 patients undergoing CABG. The study missed its primary endpoint of reduction of myocardial infarction and secondary endpoint of a composite of cardiac death, myocardial infarction, or stroke at postoperative day 4 169 . In the small subset of patients experiencing post-operative myocardial infarction, two-year mortality was reduced from 27.8% to 6.5% (p=0.006) 169 .…”
Section: Clinical Applications Of Pkc Regulatorsmentioning
confidence: 99%
“…The study missed its primary endpoint of reduction of myocardial infarction and secondary endpoint of a composite of cardiac death, myocardial infarction, or stroke at postoperative day 4 169 . In the small subset of patients experiencing post-operative myocardial infarction, two-year mortality was reduced from 27.8% to 6.5% (p=0.006) 169 . A more recent study of acadesine in CABG patients was stopped prematurely for futility after failing to show an effect on the composite outcome of 28 day mortality, nonfatal stroke, and severe left ventricular dysfunction (5.1% acadesine vs. 5% placebo) 170 .…”
Section: Clinical Applications Of Pkc Regulatorsmentioning
confidence: 99%
“…At the same time a number of clinical trials aimed at repurposing drugs that were approved for the treatment of metabolic disorders in other organs were not successful [133]. For example, Acadesine [134], a nonspecific agent targeting AMP-dependent protein kinase, L-arginine [135], an alternative energy substrate utilized in the treatment of other mitochondrial myopathies, and adenosine receptor agonists [136, 137] did not improve the conditions of myocardial infarction patients.…”
Section: Intracellular Energetic Units In Diseased Heartsmentioning
confidence: 99%